Pragmatic recommendations for the use of diagnostic testing and prognostic models in hospitalized patients with severe COVID-19 in low- and middle-income countries - Schultz, MJ; Gebremariam, TH; Park, C; Pisani, L; Sivakorn, C; Taran, S; Papali, A (American Society for Tropical Medicine and Hygiene, 2021)
Management of patients with severe or critical COVID-19 is mainly based on care for patients with severe pneumonia or acute respiratory distress syndrome (ARDS) from other causes, although some aspects of this new disease may demand a different approach. Recommendations for treatment of severe pneumonia and ARDS management have been gathered mainly from investigations in resource-rich intensive care units (ICUs), mostly located in high-income countries (HICs). It may not be practical to apply these recommendations to resource-restricted settings, particularly in low- and middle-income countries (LMICs). Indeed, high dependency units and ICUs in LMICs are frequently restricted in availability of infrastructure, equipment, medications, skilled nurses, and doctors. An international task force composed of members from LMICs and HICs, all with direct experience in various LMIC settings, critically appraised a list of questions regarding laboratory tests (including microbiology), lung imaging, and the use of diagnostic and prognostic models for patients with severe COVID-19. We provide a list of recommendations and suggestions after pragmatic, experience-based appraisal. A summary of the recommendations is shown in Table 1. Note that although these recommendations are formulated specifically for hospitalized COVID-19 patients with severe or critical disease, as defined by the WHO,1 many are applicable to patients with lower severity of disease.